The Hope-Driven Leader - Gill, Libby (Ascent Audio, 2019)
The Hope-Driven Leader is not about feel-good theory or dry data. It's an action guide informed by the thousands of people Gill has coached in both the corporate and entrepreneurial worlds around the globe. Specific skill-building topics based on research and illustrated by personal stories and case studies include: - Enhancing leadership skills - Crafting a personal brand - Becoming an influencer - Managing global teams - Handling challenges specific to women leaders Whether you are a rising star or a seasoned leader in your own business, a corporation, or your community, The Hope-Driven Leader offers you a roadmap for instilling those positive beliefs and behaviors into the core of your being and the culture of your workplace. Let the journey begin!